Low-side driving circuit and driving device - LU JIANWU (2024)
The invention discloses a low-side driving circuit and a driving device. The low-side driving circuit comprises an output transistor; the input end of the control transistor is coupled to the control end of the output transistor, and the output end of the control transistor is selectively coupled to a ground level; wherein the control transistor couples the control end of the output transistor to the ground level when the low-side driving circuit is switched to close the output, so as to quickly reduce the voltage of the control end of the output transistor. According to the low-side driving circuit provided by the invention, the turn-off delay of the output transistor can be greatly shortened, so that the output transistor can quickly enter a stage with a controllable turn-off rate, the actual driving time length and the expected driving time length are ensured to be basically matched, and the advantage of controllable turn-off speed is taken into account. 本发明揭示了一种低边驱动电路及驱动装置，所述低边驱动电路包括：输出晶体管；控制晶体管，通过其输入端耦合至